The intuitive decision preference and EEG features based on commonality heuristic - Jia, Wanying; Li, Songjie; Qian, Shao; Wang, Meng; Bao, Wei; Zhao, Jie; Cheong, Kang Hao; Xie, Nenggang (Computers in biology and medicine, 2023)
People tend to make intuitive decisions based on certain heuristics. We have observed that there is an intuitive heuristic that tends to prioritize the most common features as the selection result. In order to study the influence of cognitive limitation and context induction on the intuitive thinking of common items, a questionnaire experiment with multidisciplinary features and similarity associations is designed. The experimental results reveal the existence of three classes of subjects. The behavioral features of Class I subjects show that cognitive limitations and task context fail to induce intuitive decision-making based on common items; instead, they rely heavily on rational analysis. The behavioral features of Class II subjects show a mixture of intuitive decision-making and rational analysis, with priority given to rational analysis. The behavioral features of Class III subjects indicate that the induction of the task context reinforces the reliance on intuitive decision-making. The electroencephalogram (EEG) feature responses (mainly in the β and γ bands) of the three classes of subjects reflect their respective decision-making thinking characteristics. The event-related potential (ERP) results demonstrate that Class III subjects induce a late positive P600 component with a significantly higher average wave amplitude than the other two classes, which may be related to the “oh yes” behavior for the common item intuitive decision method. •There is a preference for intuitive decision-making based on commonality heuristic.•There are three types of decision patterns: analysis-dependent, mixed analysis with intuition, and intuition-dependent.•Differences in EEG responses and specific neural representations in three types of subjects are revealed.